Hashemite Kingdom of Jordan : Carbon Capture and Storage Capacity Building Technical Assistance - World Bank (Washington, DC, 2013)
This study was funded by the Carbon Capture and Storage (CCS) capacity building trust fund, and administered by the World Bank. The main objectives of the study were: to build or enhance Jordan s institutional capacity to make informed policy decisions on CCS technology and applications; to assess the potential application of CCS technology in Jordan; and to identify barriers-legal, regulatory, financial and others-to CCS activities in Jordan and recommend ways to address those barriers. During the course of this study, the study team concluded that Jordan may benefit from following the evolution of carbon capture and storage technology via publicly available information. Similar CCS studies are being carried out in Egypt, Morocco and Tunisia, and Jordan could benefit from a regional knowledge exchange event when those studies are concluded. However, given Jordan s other national priorities, tight government fiscal situation and limited CO2 emissions, the CCS team that authored this report believes that it is not in the interest of Jordan to pursue capital investment related to CCS in the short-term. This study, therefore, hopes to represent one step toward raising the awareness of CCS technology among Jordanian policy makers, professionals and academics. The CCS Capacity building trust fund is prepared to provide limited financial support to a team of Jordanian researchers for an exploratory study on the potential for CCS within Jordan. Such a study should further increase awareness of CCS in Jordan and create a body of knowledge within the country that could support next steps on CCS consideration by policymakers, or actual project implementation.